Targeted cross-training circuits for elite athletes - Birtwell, C. (High Performance SIRCuit, 2011)
Coaches have long recognized (he need to utilize a wide spectrum of activities to enhance the physical development of their athletes. This has lead to the usage of training modes that are outside of the target sports typical movement patterns, a practice termed "cross-training". The main goal of cross-training is to provide a varied stress on the athletes physiology and psychology. This results in a training effect that can shore up gaps in physical development and add to general and specific physical preparation goals, while avoiding overuse of sport movement patterns. A common system of cross-training employed by sport coaches is the use of circuits. Circuits typically consist of a series of loaded or calisthenics exercises executedfor a given time frame or goaf repetitions, often with restperiods between stations. The effectiveness ofsuchcircuits can be limited by an incomplete understanding of the training objective for the session as well as by the equipment typically used. This article will discuss how to design and implement cross-training circuits that are targeted towards specific training outcomes. It will also address how to integrate non-traditional forms of circuit exercise to help maximize athlete motivation and physical development.